The Important of the Family Roles in Building the Children’s Character - Hairullah (Global Writing Academica Researching and Publishing, 2023)
The family has an essential role in education, both in the community since the family is the first place where a child grows up and gets influenced by its members at a critical time in a child's education. Family is the first environment for children. The child's development in the family is determined by the situation, the family conditions, and the parents` experiences because in the family there is a natural mutual interaction based on responsibility so that a whole and solid unity will appear. Cultivating religious values such as faith, worship, honesty, and other noble principles; and Providing supervision actions for children's behavior.